New corticioid taxa in Phanerochaetaceae (Polyporales, Basidiomycota) from East Asia - Li, Yue; Chen, Che-Chih; He, Shuang-Hui (Frontiers in Microbiology, 2023)
The species diversity, taxonomy, and phylogeny of five corticioid genera of Phanerochaetaceae, Hyphodermella, Roseograndinia, Phlebiopsis, Rhizochaete, and Phanerochaete in East Asia are studied by using morphological and molecular methods. Phylogenetic analyses were performed separately for the Donkia, Phlebiopsis, Rhizochaete and Phanerochaete clades based on ITS1-5.8S-ITS2 and nrLSU sequence data. Totally, seven new species are found, and two new combinations and a new name are proposed. In the Donkia clade, Hyphodermella sensu stricto was strongly supported with two new lineages, named H. laevigata and H. tropica were recovered. Hyphodermella aurantiaca and H. zixishanensis are members of Roseograndinia, while R. jilinensis is proved to be a later synonym of H. aurantiaca. In the Phlebiopsis clade, P. cana sp. nov. was found on bamboo from tropic Asia. In the Rhizochaete clade, four new species, R. nakasoneae, R. subradicata, R. terrestris and R. yunnanensis were recovered based mainly on molecular analyses. In the Phanerochaete clade, P. subsanguinea nom. nov. is proposed to replace Phanerochaete rhizomorpha C.L. Zhao & D.Q. Wang, which is illegitimate because it was published after Phanerochaete rhizomorpha C.C. Chen, Sheng H. Wu & S.H. He representing another species. Descriptions and illustrations are provided for the new species, and discussions are given for new taxa and names. Identification keys to Hyphodermella species worldwide and Rhizochaete species in China are given separately.